2014
DOI: 10.1586/14787210.2014.959497
|View full text |Cite
|
Sign up to set email alerts
|

A risk for non-sexual transmission of human papillomavirus?

Abstract: Human papillomaviruses (HPVs) are estimated to be the most common sexually transmitted virus in humans. The virus is of great interest as it is the etiological agent of cervical cancer. Sexual transmission of HPV is generally accepted, however, non-sexual transmission of the virus is often debated. Here, we review the evidence from basic research and clinical studies that show HPV can survive well outside of its host to potentially be transmitted by non-sexual means. In doing so, we hope to discover problems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 61 publications
0
63
0
1
Order By: Relevance
“…37 The factors increasing the risk of oral HPV infection, progression, and persistence ultimately leading to head and neck cancer remain unclear, and longitudinal studies will help answer these questions. Our findings confirm that HPV explains most of the association between oral sex behaviors and OPC risk in a sample of Canadians.…”
Section: Discussionmentioning
confidence: 99%
“…37 The factors increasing the risk of oral HPV infection, progression, and persistence ultimately leading to head and neck cancer remain unclear, and longitudinal studies will help answer these questions. Our findings confirm that HPV explains most of the association between oral sex behaviors and OPC risk in a sample of Canadians.…”
Section: Discussionmentioning
confidence: 99%
“…Little to nothing is known about human papillomavirus (HPV) susceptibility to disinfection. However, it is known that these viruses are stable and able to remain infectious on surfaces, even if the surfaces are treated with common disinfectants, according to studies both in the laboratory and in healthcare scenarios (Ryndock and Meyers ). Meyers and coworkers tested the susceptibility of high‐risk HPV (HPV16) to clinical disinfectants, and showed that commonly used clinical disinfectants, including those used as sterilants in medical and dental healthcare facilities, have no effect on HPV16 infectivity, thus suggesting the possibility of fomite or nonsexual transmission of HPV16 (Meyers et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, indirect modes of transmission, such fomites or contaminated waters, cannot entirely be ruled out (Czegledy 2001;Ryndock and Meyers 2014). In the present study, HPVs have been detected in rivers samples.…”
Section: Discussionmentioning
confidence: 46%
“…HPV is one of the most common causes of sexually transmitted diseases worldwide. Non-sexual transmission of the virus is debated but recent findings shows that HPV can survive well outside of its host to potentially be transmitted by non-sexual means (Ryndock and Meyers 2014).…”
Section: Introductionmentioning
confidence: 99%